Bebe sdn. bhd. / Adila Ahmad Nazri...[et al.] - Ahmad Nazri, Adila; Muhamad Salleh, Nor Erma Afzan; Hamdan, Nur Syamimi; Abd Hanid, Nurool Atiqah; Abdul Latif, Nurul Hanisah; Shafei, Nurul Nadia (2015)
Bebe Sdn Bhd is a company that fully owned and managed by bumiputera. The company is headquartered in Shah Alam, Selangor. The company has been establised in the first quarter of 2015 and responsible for manufacturing of large scale of baby products. The existence of the company was approved and certified by Companies Commission of Malaysia (SSM). Bebe Sdn Bhd is a brand new company which has a speciality in producing and inventing different concept of baby product in the market based on latest wishes and trends alongside some user-friendly features. As the company has acquired more knowledges and experiences in this particular filed, Bebe has recognized and discovered the fact that most of the parents are hoping to give their best in many aspects for their children and definitely baby nutrition formula is not excluded in this case. The company is devoting more on services and quality of the products. The products are offered at affordable price and guaranteed with high quality products with some special features.The new concept of this products with new technology and user friendly product are highly believed to give customer's satisfaction to the maximum. The significant reason of choosing Shah Alam as our operating location is because of the middle to high income groups among Shah Alam's residents whichmay give better opportunity to dominate the market. We are starting the business with the total capital of RM250,000 and all of the partners are contributing RM60.000. We have six workers that is general manager, administration manager, operational manager, marketing manager, financial manager, and one from the operational department. Our market target of customers' characteristic is more focusing on medium to high income groups. However, the product is still considered and offered at affordable price since we also introduce the products to rural areas that have majority of low income groups